summaryrefslogtreecommitdiff
path: root/test/basic/linker.txt
diff options
context:
space:
mode:
Diffstat (limited to 'test/basic/linker.txt')
-rw-r--r--test/basic/linker.txt141
1 files changed, 0 insertions, 141 deletions
diff --git a/test/basic/linker.txt b/test/basic/linker.txt
deleted file mode 100644
index ea3ba180..00000000
--- a/test/basic/linker.txt
+++ /dev/null
@@ -1,141 +0,0 @@
-ast -> linkers = {
- ['g|"X"|"Y"|"Z"'] = {src1, src2, src3},
- ['g|"X"|"Y"'] = {src4, src5, src6},
- ['g|"X"'] = {src7, src8, src9},
- ['l|7'] = {src10},
- ['l|7|"x"'] = {src11},
- ['l|11|"k"'] = {src12},
-}
-
-```lua
-x.y.<?z?> = <!f!>
-
-<?g?> = x.y.z
-
-t.<!z!> = 1
-x.y = t
-
-x = {
- y = {
- <!z!> = 1
- }
-}
-```
-
-expect: 'l|x|y|z'
-forward: 'l|x|y|z' -> f
-backward: 'l|x|y|z' -> g
-last: 'l|x|y' + 'z'
-
-expect: 'l|x|y' + '|z'
-forward: 'l|t' + '|z' -> 'l|t|z' -> t.z
-backward: nil
-last: 'l|x' + '|y|z'
-
-expect: 'l|x' + '|y|z'
-forward: 'l|0' + '|y|z' -> 'l|0|y|z'
-backward: nil
-last: nil
-
-expect: 'l|0|y|z'
-forward: nil
-backward: nil
-last: 'l|0|y' + '|z'
-
-expect: 'l|0|y' + '|z'
-forward: 'l|1'+ '|z' -> 'l|1|z' -> field z
-backward: nil
-last: 'l|0' + '|y|z'
-
-
-```lua
-a = {
- b = {
- <?c?> = 1,
- }
-}
-
-print(a.b.<!c!>)
-```
-
-expect: 't|3|c'
-forward: nil
-backward: nil
-last: 't|3' + '|c'
-
-expect: 't|3' + '|c'
-forward: nil
-backward: 't|2|b' + '|c'
-last: nil
-
-expect: 't|2|b|c'
-forward: nil
-backward: 't|2|b' + '|c'
-last: nil
-
-```lua
----@return <?A?>
-local function f()
-end
-
-local <!x!> = f()
-```
-
-'d|A'
-'f|1|#1'
-'f|1' + '|#1'
-'l|1' + '|#1'
-'s|1' + '|#1'
-
-```lua
----@generic T
----@param a T
----@return T
-local function f(a) end
-
-local <?c?>
-
-local <!v!> = f(c)
-```
-
-'l1'
-'l2|@1'
-'f|1|@1'
-'f|1|#1'
-
-```
----@generic T
----@param p T
----@return T
-local function f(p) end
-
-local <?r?> = f(<!k!>)
-```
-
-l:r
-s:1#1 call
-l:f#1 call
-f:1#1 call -> f:1&T = l:k
-l:f@1 --> 从保存的call信息里找到 f:1&T = l:k
-l:k
-
-
-
-```
----@generic T, V
----@param p T
----@return fun(V):T, V
-local function f(p) end
-
-local f2 = f(<!k!>)
-local <?r?> = f2()
-```
-
-l:r
-s:2|#1 call1
-l:f2|#1 call1
-f:2|#1 call1
-s:1#1|#1 call2
-f:1#1|#1 call2 -> f:1&T = l:k
-dfun:1|#1
-dn:V -> f:1&T = l:k